Study versus television - Martin Browning; Eskil Heinesen (IZA Journal of Labor Economics, 2014)
The great majority of studies on the effect of school quality on academic outcomes do not take account of changes in student choices concerning effort if school quality, e.g. class size, changes. We show that empirical estimates of the "total" effect of changes in school quality could be quite different from the "partial" effect holding other inputs (including student effort) constant. The main parameters governing this difference are the extent to which inputs in the education production function are substitutes or complements and how kinked is the benefit from a higher mark. The difference depends also on student ability, the student's distaste for effort and the curvature of the education production with respect to effort.
Keywords: I21; I28; 330; Educational economics; Human capital; Effect of school quality; Student effort; Structural modelling; Education production function